Palbociclib Combined with Fulvestrant in Premenopausal Women with Advanced Breast Cancer and Prior Progression on Endocrine Therapy: PALOMA‐3 Results. (26th June 2017) - Loibl, Sibylle; Turner, Nicholas C.; Ro, Jungsil; Cristofanilli, Massimo; Iwata, Hiroji; Im, Seock‐Ah; Masuda, Norikazu; Loi, Sherene; André, Fabrice; Harbeck, Nadia; Verma, Sunil; Folkerd, Elizabeth; et al.
Abstract : Background: The efficacy and safety of palbociclib, a cyclin‐dependent kinase 4/6 inhibitor, combined with fulvestrant and goserelin was assessed in premenopausal women with advanced breast cancer (ABC) who had progressed on prior endocrine therapy (ET). Patients and Methods: One hundred eight premenopausal endocrine‐refractory women ≥18 years with hormone receptor–positive (HR+)/human epidermal growth factor receptor 2–negative (HER2−) ABC were among 521 women randomized 2:1 (347:174) to fulvestrant (500 mg) ± goserelin with either palbociclib (125 mg/day orally, 3 weeks on, 1 week off) or placebo. This analysis assessed whether the overall tolerable safety profile and significant progression‐free survival (PFS) improvement extended to premenopausal women. Potential drug‐drug interactions (DDIs) and ovarian suppression with goserelin were assessed via plasma pharmacokinetics and biochemical analyses, respectively. (ClinicalTrials.gov identifier: NCT01942135) Results: Median PFS for premenopausal women in the palbociclib ( n  = 72) versus placebo arm ( n  = 36) was 9.5 versus 5.6 months, respectively (hazard ratio, 0.50, 95% confidence interval: 0.29–0.87), and consistent with the significant PFS improvement in the same arms for postmenopausal women. Any‐grade and grade ≤3 neutropenia, leukopenia, and infections were among the most frequent adverse events reported in the palbociclib arm with concurrent goserelin administration. Hormone concentrations were similar between treatment arms and confirmed sustained ovarian suppression. Clinically relevant DDIs were not observed. Conclusion: Palbociclib combined with fulvestrant and goserelin was an effective and well‐tolerated treatment for premenopausal women with prior endocrine‐resistant HR+/HER2− ABC. Inclusion of both premenopausal and postmenopausal women in pivotal combination ET trials facilitates access to novel drugs for young women and should be considered as a new standard for clinical trial design. Abstract : In the randomized, phase III PALOMA‐3 trial, palbociclib plus fulvestrant (6 goserelin) prolonged investigator‐assessed progression‐free survival compared with placebo plus fulvestrant (6 goserelin) in women with HR1/HER2‐ advanced breast cancer after prior progression on endocrine therapy. PALOMA‐3 was the first registrational study to include premenopausal women in this setting; in this article, results are described by menopausal status, with a focus on premenopausal women with prior endocrine‐resistant HR1/HER2‐ advanced breast cancer.